Construction of interconnected NiO/CoFe alloy nanosheets for overall water splitting. (July 2022) - Lei, Yuanting; Zhang, Lili; Zhou, Danni; Xiong, Chengli; Zhao, Yafei; Chen, Wenxing; Xiang, Xu; Shang, Huishan; Zhang, Bing
Abstract: Electrocatalytic overall water splitting is considered to be a promising strategy for hydrogen production. However, the development of high-efficient and robust bifunctional catalysts with earth-abundant elements for water splitting is of great significance. Herein, interconnected CoFe alloy nanosheets supported on NiO nanosheets (NiO/CoFe alloy) were synthesized on carbon cloth via a simple electrochemical activation of NiO/CoFe-layered double hydroxide (NiO/CoFe-LDH). The as-prepared NiO/CoFe alloy exhibits excellent activity and durability toward HER (hydrogen evolution reaction) and OER (oxygen evolution reaction). Impressively, it requires comparatively low overpotentials of 218 and 280 mV to deliver the current density of 10 and 30 mA cm −2 for HER and OER in 1.0 M KOH, respectively. The superior catalytic behavior may derive from the interconnected nanosheets structure, abundant exposed active sites, and the fast electron transfer of NiO/CoFe alloy. This work may shed light on the rational construction and design of precious metal-free catalysts with remarkable performance for overall water splitting and beyond. Graphical abstract: Image 1 Highlights: A novel method of electrochemical activation is used to synthesize NiO/CoFe alloy. NiO/CoFe alloy possesses an interconnected nanosheet structure. Abundant active sites and fast electron transfer promote electrocatalytic process. NiO/CoFe alloy achieves excellent activity and durability toward HER and OER.